Arbitration Practice of Recognitionand Administration of the Execution of Foreign Arbitration Decisionsin the Russian Federation - L. M. Churkina (Сибирское юридическое обозрение, 2018)
The Author considers the process of recognition and enforcement of foreign arbitral decision on economic disputes in the Russian Federation in order to identify problems arising in arbitration proceedings in the performance of foreign arbitral decision. Characteristic features of application of the international multilateral treaties ratified by the Russian Federation and regulating process of recognition and enforcement of the foreign arbitration decision are allocated and described. The article analyzes other grounds for recognition and enforcement of a foreign arbitral decision, except for international treaties. The article substantiates the idea that the Russian arbitration practice in the category of cases specified in the article is in the process of development and improvement. On the basis of the research, the Author concludes that at present Russian arbitration courts often refer to the principle of international courtesy and the principle of reciprocity in considering the application of companies for recognition and enforcement of foreign arbitral decision in economic disputes. The issue of procedural features related to the provision of evidence to ensure the principle of reciprocity continues to be debated.